1989
DOI: 10.1139/v89-344
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of ammonia in chloroform: analysis in terms of Henry's law and the equilibrium constant for hydrogen-bonded complex formation

Abstract: . 67,2213 (1989). We have measured the solubility of ammonia in chloroform at several pressures and at three temperatures (25,30, and 35°C). Results of these measurements have been analysed in terms of the Henry's law constant that applies to "simple" dissolution of the type B(g) = B(disso1ved) and the equilibrium constant K for the liquid phase complex-forming equilibrium represented by A + B = AB where A and B represent chloroform and ammonia, respectively. As expected on the basis of this analysis, ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It has been previously reported that the mole fraction solubility of ammonia (as NH 3 ) in chloroform is 0.1-0.2, with ca. 70% of it being in the free form, and the remainder as a 1:1 H-bonded complex with this solvent [58]. Therefore, it is anticipated that NH 3 will also have significant solubility in edible oils, such as CLOs.…”
Section: Detection and Antioxidant Potential Of Ammonia In The Fermented Clo Productmentioning
confidence: 99%
“…It has been previously reported that the mole fraction solubility of ammonia (as NH 3 ) in chloroform is 0.1-0.2, with ca. 70% of it being in the free form, and the remainder as a 1:1 H-bonded complex with this solvent [58]. Therefore, it is anticipated that NH 3 will also have significant solubility in edible oils, such as CLOs.…”
Section: Detection and Antioxidant Potential Of Ammonia In The Fermented Clo Productmentioning
confidence: 99%
“…complexes are formed can involve explicit recognition of the complex by way of an appropriate equilibrium constant, as done previously for volumes of SO, in various solvents (1 1) and for solubilities of NH3 in HCC1, (15).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction was carried out in a Drechsel gas bottle [34], containing a chloroform solution of 4f or 5f and equipped with a stirring bar, through passing a continuous stream of ammonia gas (dried over a column of soda lime). Chloroform was chosen as the reaction solvent, since ammonia has a considerable solubility in it through hydrogen bond formation [35]. Unlike a previously published work [33], aqueous ammonia solution was not used in order to avoid hydrolysis of 4f and 5f into the carboxylic acids of the monoanilides 4d and 5d and thiocyanic acid [36].…”
Section: General Synthesis Of N-adipoyl Monoanilide Thiourea and N-pimentioning
confidence: 99%